A chance constrained programming method to determine optimal capital structure for privatized infrastructure. Issue 7 (3rd July 2021) - Wang, Xiuqin; Wang, Bing; Xu, Yantao; Shi, Lanmin
Abstract: Capital structure optimization is an important aspect to ensure the success of public–private partnership (PPP) financing. Existing optimization methods fail to provide certain confidence level of the optimization result of PPP capital structure. The aim of this paper to optimize the capital structure of PPP projects by developing a chance-constrained programming (CCP) method with a certain confidence level under project risks. The results show that compared with existing methods, CCP method yields a greater optimal equity share, smaller NPV value, and higher confidence level depending on private sector's risk preference. Besides, the optimal equity share is mainly determined by banks' requirement and government regulation on commitment and it shrinks as banks' risk preference grows. Theoretical calculation and simulation technique were adopted to make the result more convincing. The paper can help the private sector to more reasonably and reliably determine the optimal capital structure according to their risk preference.